Further trials with seed dressings for the control of leaf stripe Pyrenophora avenae in Northern Ireland oats - Kanapathipillai, Vijaya S.; Malone , J. P.; McGimpsey, H. C. (Ministry of Agriculture, Northern Ireland, 1975)
Significantly better control of leaf stripe of oats caused '9Y mercury tolerant Pyrenophora avenae was obtained by the use of a proprietary fungicide containing organomercury + carboxin than by the use of one containing only organomercury but there was not a significant difference between organomercury + carboxin and carboxin alone. Three other experimental materials gave results not significantly different from. those for organomercury but they were phytotoxic.